Given the definitions of f(x)f(x) and g(x)g(x) below, find the value of (f\circ g)(-4).(f∘g)(−4). f(x)= f(x)= \,\,3x^2+4x-3 3x 2
+4x−3 g(x)= g(x)= \,\,-2x-11 −2x−11
1 answer:
Answer:
(f∘g)(−4) = 12
Step-by-step explanation:
Given the functions
f(x)= 3x^2 + 4x - 3
g(x) = -2x-11
Required
(f∘g)(−4)
(f∘g)(x) = f(g(x))
f(g(x)) = f(-2x-11)
f(-2x-11) = 3(-2x-11)^2 + 4(-2x-11) - 3
f(g(x)) = 3(-2x-11)^2 + 4(-2x-11) - 3
f(g(-4)) = 3(-2(-4)-11)^2 + 4(-2(-4)-11) -3
f(g(-4)) = 3(8-11)^2 + 4(8-11) - 3
f(g(-4)) = 3(-3)^2 + 4(-3) - 3
f(g(-4)) = 3(9) - 12 - 3
f(g(-4)) = 27 - 15
f(g(-4)) = 12
Hence (f∘g)(−4) = 12
You might be interested in
70.6 what i got was 70.6753275399
15 units because I need to have
-2* F
You do +3 +2 -4 -1 which equals to 0. Then you do 0 plus -2 which equals -2*F.
Answer:
i tink it is store A
Step-by-step explanation:
because it has the large medium value.. hope this answer helpes you..